2022
DOI: 10.1136/bmjopen-2021-051317
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety symptoms and their determinant factors among patients with cancer in southern Ethiopia: a cross-sectional study

Abstract: ObjectiveThe study was aimed to assess the prevalence of depression and anxiety symptoms and their determinant factors among patients with cancer attending follow-up at Hawassa University Comprehensive Specialized Hospital cancer treatment centre, Ethiopia.DesignInstitution-based cross-sectional study design was implemented.SettingPatients with cancer at Hawassa University Comprehensive Specialized Hospital cancer treatment centre from October 2019 to December 2019.ParticipantsRandomly selected 415 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 59 publications
(122 reference statements)
4
35
1
2
Order By: Relevance
“…However, the estimate was still high considering that depression increases the risk of mortality by 19% among patients living with cancer [13,17]. Our estimate also fell within 3-58% reference ranges for major depressive disorders among cancer patients as reported elsewhere [9,10,[15][16][17]28].…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…However, the estimate was still high considering that depression increases the risk of mortality by 19% among patients living with cancer [13,17]. Our estimate also fell within 3-58% reference ranges for major depressive disorders among cancer patients as reported elsewhere [9,10,[15][16][17]28].…”
Section: Discussionsupporting
confidence: 66%
“…To our knowledge, this study had reported lower prevalence estimate for major depressive disorder in the sub-Saharan Africa among patients living with cancer when compared with other reports in the region [9,17,[23][24][25][26][27]. However, the estimate was still high considering that depression increases the risk of mortality by 19% among patients living with cancer [13,17].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations